2021
DOI: 10.51477/mejs.947973
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Evaluation of Ester Derivatives of 4-(Diethylamino)salicylaldehyde as Cholinesterase, and Tyrosinase Inhibitors

Abstract: Alzheimer's disease, one of the diseases that still has no a specific therapy, has become a major public health issue owing to the increasing population of the elderly, particularly in rich countries. Inhibitory of cholinesterase enzymes (acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), which hydrolyze acetylcholine (ACh) and butyrylcholine (BCh) neurotransmitters, have recently become a choice for the therapy of this disease. Therefore, there is currently a great demand for novel enzyme inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In this research, the inhibitory performance of new compounds towards cholinesterases was determined, respectively [32]. The method used in the present study was explained in detail in our previous studies [27,29,31,33].…”
Section: General Procedures For Determining the Anticholinesterase Ac...mentioning
confidence: 99%
“…In this research, the inhibitory performance of new compounds towards cholinesterases was determined, respectively [32]. The method used in the present study was explained in detail in our previous studies [27,29,31,33].…”
Section: General Procedures For Determining the Anticholinesterase Ac...mentioning
confidence: 99%
“…In the recent years, the incidence of AD is increasing, especially in people over 60 years of age, and it is seen that this disease has become a cause of serious morbidity. [3][4][5][6] Studies have been carried out for many years to reveal the causes of the disease; and as a result of these studies, it is stated that the most important pathological lesions suggested in the formation of AD are amyloid plaques and neurofibrillary tangles. [7,8] On the other hand, various hypotheses have been put forward in the formation of AD, the most important of which is the cholinergic hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the incidence of AD is increasing, especially in people over 60 years of age, and it is seen that this disease has become a cause of serious morbidity. [ 3–6 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, it is reported that these inhibitors have serious side effects in clinical application [11,14] . Therefore, there is a great need for the development of new cholinesterase inhibitors [15a–e] …”
Section: Introductionmentioning
confidence: 99%
“…It is reported in many studies that these compounds have various biological activities in a wide broad spectrum including antioxidant [28b,29a–c] , anticonvulsant [30] , antidepressant [31] , antimicrobial [32] and antitumoral [33] and so forth. On the other hand, it is well known that hydrazone derivatives also act as AChE, BChE and tyrosinase inhibitors [15d,28e, 29b, 34] . Apart from that, they indicate various biological activities such as analgesic and anti‐inflammatory [35a–b] …”
Section: Introductionmentioning
confidence: 99%